Big boss - Gallardo, Cesar (Manila Aquarius Records & Tapes, 1965)
Big Boss is a story of Adolfo and Fernando who grew up from different world and fate allowed them to met one day and discovered that they are not just kin but even identical twins. Their real father who was tagged as mysterious Big Boss used his influence to again bind their umbilical cord but life is really too short for a reunion for their father... and even for Fernando.
VCD
Executive producer Rosalinda Magno ; directed by Cesar Gallardo.
Joseph Estrada; Cynthia Ugalde; Eva Montes
Keywords: Feature Films